How Corruption Is and Should Be Investigated by Economic Theory - Petr Wawrosz (Economies, 2022)
The article analyzes how economic theory usually investigates corruption. It describes the main traditional economic theories dealing with this issue—principal-agent theory (agency theory) and rent-seeking theory—and it emphasizes that both face some problems, especially their neglect of some important factors as to why corruption occurs which prevents them from accurately analyzing this phenomenon and proposing solutions on how to fight against it. The article further discusses whether institutional economics can overcome these problems. We show that it does, but that it needs to more seriously consider the environment in which corruption occurs. Redistribution system theory can serve as a useful aid here because it reveals that the source of corruption is an environment of undesirable redistribution. The article provides the characteristics of this type of redistribution and shows how its reduction also leads to the reduction in corruption. It can be concluded that economic theory should not rely only on traditional approaches to corruption but should at least add institutional economics and redistribution system theory to its methods of corruption analysis.